The Implementation of Storytelling in Learning Bahasa Indonesia to develop Students' Emotional Intelligence - Yumna Gina Mustika; Kustiarini Kustiarini (UIN Raden Mas Said Surakarta, 2022)
This descriptive study investigates the implementation of storytelling in learning Bahasa Indonesia to develop second graders’ emotional intelligence. This study was conducted at SDIT Insan Mulia Surakarta from February to September 2021. This study involved the principal, teacher and several students of class 2C, and other teachers teaching the second grade. Data collection techniques were interviews, observation, and documentation. The storytelling was carried out through planning, implementation, and evaluation. Storytelling was carried out using images. From this study, self-confidence, responsibility, and tolerance are examples of emotional intelligence that emerge through the storytelling for learning Bahasa Indonesia.